The multi-process reaction model and underlying mechanisms of 2, 4, 6-trichlorophenol removal in lab-scale biochar-microorganism augmented ZVI PRBs and field-scale PRBs performance. (15th June 2022) - Wang, Wenbing; Gong, Tiantian; Li, Hui; Liu, Yiming; Dong, Qianling; Zan, Rixia; Wu, Yulin
Highlights: The reaction rate of 2, 4, 6-TCP increased by 175% in the combined chemical-biological system. Two-site sorption coupling chemical-biological reaction model was developed for optimizing Bio-PRBS. Chemical-biological augmentation significantly improved the retardation effect of BIO-PRBS for 2, 4, 6-TCP. Versatile functional bacteria desulfitobacterium was crucial in the transformation of Fe (III) iron oxides. The diversity and richness of archaea in the reaction solution were improved by ZVI gel beads addition. Abstract: This work developed calcium alginate (CA) embedded zero-valent iron (ZVI@CA) and CA embedded biochar (BC) immobilized microorganism (BC&Cell@CA) gel beads as alternative to conventional Fe 0 permeable reactive barriers for treating groundwater contaminated with 2, 4, 6-trichlorophenol (2, 4, 6-TCP). Lab-scale and field-scale biochar-microorganism augmented PRBs (Bio-PRBs) were constructed and tested. The underlying mechanisms were revealed by a multi-source data calibrated multi-process reaction model, X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and high-throughput sequencing. Moreover, calibrated advection-dispersion ( a ) coupled with the two-site sorption ( K d ) and chemical-biological multi-process reaction ( λ ) model were used for revealing 2, 4, 6-TCP transport behavior and optimizing Bio-PRBs. Compared to that in the ZVI@CA (0.004 h –1 ) system, the reaction rate (0.011 h –1 ) of 2, 4, 6-TCP increased by 175% in the combined chemical-biological batch system. Moreover, chemical-biological augmentation significantly improved the retardation effect of Bio-PRBs for 2, 4, 6-TCP. It came from that chemical-biological augmentation significantly decreased the dispersivity a (0.53 to 0.20 cm), and increased the distribution coefficient K d (2.20 to 19.00 cm 3  mg –1 ), the reaction rate λ (2.40 to 3.60 day –1 ), and the fraction (30% to 80%) of first-order kinetic sorption of 2, 4, 6-TCP in the lab-scale one-dimensional Bio-PRBs. Moreover, versatile functional bacteria Desulfitobacterium was crucial in the transformation of Fe (III) iron oxides. The diversity and richness of archaea in the reaction solution were improved by ZVI@CA gel beads addition. Furthermore, the field-scale reaction system was designed to remediate the chlorinated organic compounds and Benzene Toluene Ethylbenzene & Xylene contaminated groundwater in a pesticide factory site. The field test results demonstrated it is a promising technology to construct vertical reaction columns or horizontal Bio-PRBs for the efficient remediation of actually contaminated groundwater. Graphical abstract: Image, graphical abstract